2001
DOI: 10.1053/jhep.2001.25512
|View full text |Cite
|
Sign up to set email alerts
|

High Amino Acid Variability Within the Ns5a of Hepatitis C Virus (Hcv) Is Associated With Hepatocellular Carcinoma in Patients With Hcv–1B-Related Cirrhosis

Abstract: Hepatitis C virus (HCV) is an enveloped, single-stranded RNA virus that belongs to the Flaviviridae family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 71 publications
3
42
0
Order By: Relevance
“…The genetic distance between these 10 isolates was similar to that previously documented among viral isolates in other instances of HCV transmission through different mechanisms, such as colonoscopy (4), mother to infant (20,31), and others (19,28,29). In contrast, the genetic distance between virus from the remaining two cases was much greater and similar to that previously described among epidemiologically unrelated strains from the same geographical area (9,24,25,27), suggesting that these individuals were not involved in the epidemic outbreak under consideration. Close genetic relatedness of these 10 isolates was confirmed by phylogenetic analysis, since all of them clustered together with high bootstrap values and were clearly separated from the remaining samples analyzed (Fig.…”
supporting
confidence: 85%
“…The genetic distance between these 10 isolates was similar to that previously documented among viral isolates in other instances of HCV transmission through different mechanisms, such as colonoscopy (4), mother to infant (20,31), and others (19,28,29). In contrast, the genetic distance between virus from the remaining two cases was much greater and similar to that previously described among epidemiologically unrelated strains from the same geographical area (9,24,25,27), suggesting that these individuals were not involved in the epidemic outbreak under consideration. Close genetic relatedness of these 10 isolates was confirmed by phylogenetic analysis, since all of them clustered together with high bootstrap values and were clearly separated from the remaining samples analyzed (Fig.…”
supporting
confidence: 85%
“…This region has a particular importance since previous work by Enomoto et al [148] (1995) suggested that the genetic heterogeneity of the interferon sensitivity determining region domain of HCV NS5A (IFN sensitivity-determining region), linked to response to therapy in Japanese patients [148] . Although there seems not to be a consensus on this issue [85] , the published information supports the hypothesis that an association indeed exists between NS5A and response to therapy [149][150][151] . Some reports suggest that HCV NS5A protein can act in vivo repressing PKR function, and presumably allowing HCV to escape the antiviral effects of interferon [1,3,152,153] .…”
Section: Recombinationmentioning
confidence: 88%
“…HCV-RNA was extracted from serum by the Trizol method following the instructions of the manufacturer (Invitrogen). Specific amplification of HCV-RNA was carried out with primers described previously (Gimenez-Barcons et al, 2001) as follows: cDNA was synthesized from viral RNA using 1?5 mM reverse primer HV2 and 0?45 U AMV reverse transcriptase ml 21 in 20 ml final volume. Ten microlitres of this cDNA was used as a template for PCR amplification using the forward primer HV1 and the reverse primer HV2 at 0?5 mM each, in a final volume of 50 ml.…”
Section: Methodsmentioning
confidence: 99%